Chronic femoral artery ligation exaggerates the pressor and sympathetic nerve responses during dynamic skeletal muscle stretch in decerebrate rats - Kempf, Evan Alexander (Kansas State University, 2017)
Mechanical and metabolic signals arising during skeletal muscle contraction reflexly increase sympathetic nerve activity and blood pressure (i.e., the exercise pressor reflex). In a rat model of simulated peripheral artery disease (PAD) in which a femoral artery is chronically (~72 hours) ligated, the mechanically-sensitive component of the exercise pressor reflex during 1 Hz dynamic contraction is exaggerated compared to that found in normal rats. Whether this is due to an enhanced acute sensitization of mechanoreceptors by metabolites produced during contraction or involves a chronic sensitization of mechanoreceptors is unknown. To investigate this issue, in decerebrate, unanesthetized rats we tested the hypothesis that the increases in mean arterial blood pressure (MAP) and renal sympathetic nerve activity (RSNA) during 1 Hz dynamic stretch are larger when evoked from a previously “ligated” hindlimb compared to those evoked from the contralateral “freely perfused” hindlimb. Dynamic stretch provided a mechanical stimulus in the absence of contraction-induced metabolite production that replicated closely the pattern of the mechanical stimulus present during dynamic contraction. We found that the increases in MAP (freely perfused: 14±1, ligated: 23±3 mmHg, p=0.02) and RSNA were significantly greater during dynamic stretch of the ligated hindlimb compared to the increases during dynamic stretch of the freely perfused hindlimb. These findings suggest that the exaggerated mechanically-sensitive component of the exercise pressor reflex found during dynamic muscle contraction in this rat model of simulated PAD involves a chronic sensitizing effect of ligation on muscle mechanoreceptors and cannot be attributed solely to acute contraction-induced metabolite sensitization.
Keywords: Exercise; Ischemia; Blood pressure; Muscle afferents; Peripheral artery disease